COVID-19 Variability Within European Countries Sourced From ECDC Data. Is Variability Explained by Specific Country Policies? - Ruano-Ravina, Alberto; López-Vizcaíno, Esther; Candal-Pedreira, Cristina; Santiago-Pérez, María Isolina; Pérez-Ríos, Mónica (Frontiers in Public Health, 2022)
Background: Europe has had a large variability in COVID19 incidence between and within countries, particularly after June 2020. We aim to assess the variability between European countries and regions located in a given country. Methods: We used ECDC information including countries having 7 regions or more. The metric used to assess the regional variability within a country was the intercuartilic range in a weekly basis for 32 weeks between June 29th 2020 and February 1st 2021. We also calculated each country’s overall variability across the 32 weeks using the distances from the regional curves of the 14-day incidence rates to the corresponding national curve, using the L2 metric for functional data. We afterwards standardized this metric to a scale from 0 to 100 points. We repeated the calculations excluding island regions. Results: The variability between and within countries was large. Slovenia, Spain and Portugal have the greatest variability. Spain and Slovenia held also the top three places for the greatest number of weeks (Spain for 19 weeks and Slovenia for 10) with the highest variability. For variability among the incidence curves across the 32-week period, Slovenia, Portugal and Spain ranked first in functional variability, when all the regions were analysed but also when the island regions were excluded. Conclusions: These differences might be due to how countries tackled the epidemiological situation. The persistent variability in COVID-19 incidence between regions of a given country suggests that governmental action may have an important role in applying epidemiological control measures.